Eksplorasi Penerapan Pembelajaran Berdiferensiasi pada Materi Data dan Diagram - Ahmad, Asdar; Salsabilah, Annisa Nabila; Assagaf, Said Fachry; Jeranah, Jeranah (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
The diverse characteristics of students in the classroom require the implementation of instructional strategies that can meet individual learning needs. Differentiated instruction is one such strategy that can accommodate this diversity, particularly in mathematics education. This study describes the application of differentiated instruction in teaching Data and Diagrams in Class VII.A at SMP Negeri 4 Sungguminasa during the 2023/2024 academic year. The study employs a qualitative descriptive method involving one mathematics teacher and 34 students as subjects. Data were collected through observation sheets, questionnaires, and documentation. The findings reveal that the teacher implemented various teaching methods, such as group discussions and the use of technology, while actively providing feedback. Despite challenges in adapting methods to meet the needs of all students, the teacher responsded positively to the implementation of differentiated instruction and recognized the need for further training. Student participation indicated that this approach enhanced understanding and motivation, although some students still required additional guidance. These findings suggest that differentiated instruction plays a role in meeting diverse learning needs in the classroom, yet further development is needed to ensure its effectiveness for all students.